Problems and prospects of solid waste management in the Republic of Kazakhstan (Journal of actual problems of jurisprudence, 2018)
The article contains information on the problems of solid domestic waste utilization in the Republic of Kazakhstan. Handling of solid household waste is one of the burning issues that require careful study and a comprehensive legal settlement. At present, there is no separate collection of solid domestic waste at the source of waste generation in Kazakhstan, therefore it is difficult to conduct a comprehensive economic evaluation across the country of waste separation systems at the source, separate waste disposal, processing and sale of recovered materials. One of the main problems of the state is increasing the efficiency, reliability, environmental and social acceptability of the complex of services for the collection, transportation, utilization, processing and disposal of solid domestic waste, increasing the share of MSW processing, and ensuring safe disposal of waste. Key words: solid household waste, right to a favorable environment, law, ecology, state.